2020
DOI: 10.1002/jcp.29518
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N‐oxide promotes apoE−/− mice atherosclerosis by inducing vascular endothelial cell pyroptosis via the SDHB/ROS pathway

Abstract: Trimethylamine N-oxide (TMAO) is produced from the phosphatidylcholine metabolism of gut flora and acts as a risk factor of cardiovascular disease.However, the underlying mechanisms for its proatherogenic action remain unclear.This study aimed to observe the effect of TMAO on endothelial cell pyroptosis and explore the underlying mechanisms. Our results showed that TMAO promoted the progression of atherosclerotic lesions in apolipoprotein E-deficient (apoE −/− ) mice fed a high-fat diet. Pyroptosis and succina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 25 publications
0
67
0
Order By: Relevance
“…As a type of proinflammatory cell death, pyroptosis is characterized by swollen cells, subcellular organelle damage, and the release of cytokines, including the NLRP3 inflammasome, NLRP6, an apoptosis-associated speck-like protein containing CARD (ASC), cysteinyl-aspartate-specific proteinase 1 (caspase-1), and gasdermin D. Data have shown that sodium butyrate is capable of breaking down the gingival epithelial barrier by inducing pyroptosis [ 52 ]. Similarly, TMAO promotes vascular endothelial cell pyroptosis via ROS production, thus resulting in the development of atherosclerosis [ 53 ]. However, Gu et al proved the antipyroptosis effects of sodium butyrate on renal glomerular endothelial cells, protecting them from damage caused by high glucose [ 54 ].…”
Section: Mechanisms Underlying the Interaction Between Gut Microbimentioning
confidence: 99%
“…As a type of proinflammatory cell death, pyroptosis is characterized by swollen cells, subcellular organelle damage, and the release of cytokines, including the NLRP3 inflammasome, NLRP6, an apoptosis-associated speck-like protein containing CARD (ASC), cysteinyl-aspartate-specific proteinase 1 (caspase-1), and gasdermin D. Data have shown that sodium butyrate is capable of breaking down the gingival epithelial barrier by inducing pyroptosis [ 52 ]. Similarly, TMAO promotes vascular endothelial cell pyroptosis via ROS production, thus resulting in the development of atherosclerosis [ 53 ]. However, Gu et al proved the antipyroptosis effects of sodium butyrate on renal glomerular endothelial cells, protecting them from damage caused by high glucose [ 54 ].…”
Section: Mechanisms Underlying the Interaction Between Gut Microbimentioning
confidence: 99%
“…With regard to the relationship between TMAO and mitochondrial dysfunctions, of interest are the data showing a coupled increase in the level of TMAO, citrate and 2-oxoglutarate in urinary metabolomic profile in model experiments in rats with active or relapsing vasculitis [ 48 ]. In addition, TMAO promoted endothelial cell pyroptosis, a programmed cell death characterized by plasma membrane rupture via mitochondrial ROS production induced by SDH upregulation [ 49 ]. According to our data, TMAO stimulated mitochondrial swelling only under acidification and did not affect either calcium-induced MPTP opening or iron-induced swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that ROS can activate NF- κ B, JNK/SAPK, and p38 MAPK signaling pathways [ 36 ]. In vascular endothelial cells, ROS can result in the upregulation of adhesion of molecule expression significantly, increase monocyte-endothelial adherence, and ultimately atherosclerosis [ 37 ]. Rains et al report that ROS can result in the increase of LFA-1 on monocytes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%